PENGARUH PEMBERDAYAAN TERHADAP TINGKAT PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DI SMP TRISOKO - Fatimah, Sundari; Alam, Nur (Universitas Mohammad Husni Thamrin, 2022)
Background : Knowledge on reproductive health is a high demand for adolescents since they start the puberty period. However, reproductive health education in Indonesia is not commonly implemented. Education is needed to prevent problems associated with reproductive health, and counseling is a particular means to educate.Objective